172k views
1 vote
Shortern this expression pls​

Shortern this expression pls​-example-1

1 Answer

4 votes

Answer:


c =(8)/(3)

Explanation:

Given


c = \sqrt{(4 + \sqrt 7)/(4 - \sqrt 7)} + \sqrt{(4 - \sqrt 7)/(4 + \sqrt 7)}

Required

Shorten

We have:


c = \sqrt{(4 + \sqrt 7)/(4 - \sqrt 7)} + \sqrt{(4 - \sqrt 7)/(4 + \sqrt 7)}

Rationalize


c = \sqrt{(4 + \sqrt 7)/(4 - \sqrt 7) * (4 + \sqrt 7)/(4 + \sqrt 7)} + \sqrt{(4 - \sqrt 7)/(4 + \sqrt 7)*(4 - \sqrt 7)/(4 - \sqrt 7)}

Expand


c = \sqrt{((4 + \sqrt 7)^2)/(4^2 - (\sqrt 7)^2)} + \sqrt{((4 - \sqrt 7)^2)/(4^2 - (\sqrt 7)^2)


c = \sqrt{((4 + \sqrt 7)^2)/(16 - 7)} + \sqrt{((4 - \sqrt 7)^2)/(16 - 7)


c = \sqrt{((4 + \sqrt 7)^2)/(9)} + \sqrt{((4 - \sqrt 7)^2)/(9)

Take positive square roots


c =(4 + \sqrt 7)/(3) + (4 - \sqrt 7)/(3)

Take LCM


c =(4 + \sqrt 7 + 4 - \sqrt 7)/(3)

Collect like terms


c =(4 + 4+ \sqrt 7 - \sqrt 7)/(3)


c =(8)/(3)

User Artisan
by
5.5k points